Perjuangan Siti Soendari Darmobroto dalam Memperjuangkan Hak-Hak Perempuan Indonesia, 1913-1914 - Akbar, Farhan; Maryuni, Yuni; Prasadana, Muhammad Anggie Farizqi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
Journalism and mass media are widely used by people not only to find out the latest news circulating in society but also as a tool to spread certain ideas and ideas so that they can influence and shape public opinion about a social phenomenon that occurs around them. they. The development of ethical politics in the Dutch East Indies in the half of the 20th century opened the gates to a historical period known as the "National Awakening". Many elite figures, encouraged by education and scientific influence from Europe, began to form various organizations and newspapers as a step in opposing the form of Dutch colonial hegemony and power in Indonesia. Even though there was progress in the Dutch East Indies with the many schools built by the colonial government during the ethical-political policy, women did not share this feeling. This encourages many of them to use mass media such as newspapers and magazines as a bridge to express their feelings and criticism of the situation they are experiencing. One of the women who is active in voicing women's issues is Siti Sundari. Through this research, the author found that Siti Sundari had an important role in her efforts to fight for women's rights in Indonesia through her ideas conveyed in writing in various mass media such as Poetri Hindia, Goentoer Berberger, Medan Bermobil, and Doenia Bermobil. He also founded the Wanito Sworo newspaper as a forum to spread his ideas about the importance of improving the position of women in society, both in terms of education, legal equality, marriage issues, and criticism of patriarchy and polygamy. Using historical methods, the author searches primary sources to reconstruct Siti Sundari's early life, her involvement and role in journalism as a mouthpiece for emancipation, and her role in advancing the rights of Indonesian women in the 1913-1914 period through her speeches at various congresses and important meetings discussing the issue of women's emancipation.